KAJIAN IKONOLOGI IKLAN TELEVISI SUSU FORMULA NUTRILON ROYAL TIGA VERSI â€œLIFE IS AN ADVENTUREâ€ - NANIWATI SULAIMAN (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Comparing to other milk-formula advertisements, Nutrilon RoyalÂ 3 â€œLife is an Adventureâ€ version is one of the TV commercial which has got the most appreciation and positive response from various circles of society.The success of this ads does not solely lie in its visual creativity but is also determined by its suitability with the psychosocial cultural of the society. This research would like to reveal the message and the meaning behind the visual appearance of the Nutrilon Royal ads which is able to enchant the consumers by using the theory of analytic iconology of Erwin Panofsky. The TV commercial of Nutrilon Royal 3 is using the indirect approach, spontaneous, outdoor, multi-racial children, natural and poetic. Nutrilon Royal main target is the young mothers who live in big cities with the children who generally spend their time indoors. Nutrilon Royal strategy in attracting the metropolis interest is, among others showing the scenes of children who are free and dare to be active in the broad of nature, representing the courage and physical strength in facing the nature as well as friendly, adaptive, even enjoy and become one with the nature. Through this film, embedded the image of Nutrilon Royal 3 as a milk-formula that gives health, freedom, strength and courage to the children in going through their lives.Â Keywords: advertisement; children; free; milk formula; nature